Biochar loaded sulfur modified zero-valent iron material and application thereof in groundwater remediation

By loading sulfur to modify zero-valent iron in biochar to form a core-shell structure, the problem of zero-valent iron agglomeration and poor stability in water treatment is solved, the stability and catalytic performance of the material are improved, and efficient pollutants are achieved Removal effect.

CN119281284APending Publication Date: 2025-01-10EAST CHINA UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411423446.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Zerovalent iron is prone to agglomeration in water treatment, reducing dispersion and treatment efficiency, and has poor stability and prone to aging, which limits its long-term effectiveness.

Method used

By loading sulfur to modify zero-valent iron in the porous structure of biochar, a core-shell structure is formed. Iron sulfide serves as the shell to protect the zero-valent iron core, and combines the porous and active catalytic sites of biochar to improve the stability and reaction of the material. active.

Benefits of technology

It significantly improves the stability and catalytic properties of the material and enhances the adsorption and degradation capabilities of pollutants. Especially in the treatment of uranium and metronidazole, the removal rate reaches 97% and 98%, making it suitable for industrial large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281284A_ABST
    Figure CN119281284A_ABST
Patent Text Reader

Abstract

The invention provides a biochar loaded sulfur modified zero-valent iron material and application thereof in groundwater remediation, and particularly relates to the technical field of inorganic materials. According to the biochar-loaded sulfur-modified zero-valent iron material, sulfur-modified zero-valent iron is loaded in a porous structure of biochar; the sulfur modified zero-valent iron has a core-shell structure; wherein the inner core of the core-shell structure is zero-valent iron, and the outer shell of the core-shell structure is iron sulfide. According to the biochar-loaded sulfur-modified zero-valent iron material provided by the invention, a sulfide layer is formed on the surface of zero-valent iron, so that a zero-valent iron core is prevented from being in direct contact with water or dissolved oxygen, and the durability of the zero-valent iron core is improved. Delocalized electrons in the sulfide layer promote the electron transfer process, and the catalytic performance of the material is enhanced. The biochar loaded sulfur modified zero-valent iron material provided by the invention is high in stability and wide in application range. Due to the multifunctionality of the material, the material has potential application value in a plurality of fields such as environmental restoration and pollutant degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic materials, and in particular to a biochar-loaded sulfur-modified zero-valent iron material and an application thereof in groundwater remediation. Background Art

[0002] Zero Valent Iron (ZVI) is a long-standing water treatment material with an application history of more than 130 years. It effectively removes metal and organic pollutants from groundwater and wastewater mainly through redox reactions and adsorption of iron corrosion products. Thanks to the abundant content of iron in the earth's crust, the cost of using zero-valent iron is relatively low. In addition, zero-valent iron also has a strong reducing ability, and its reduction potential is -0.44V, which enables it to reduce a variety of pollutants. At the same time, as an environmentally friendly remediation medium, it is not easy to cause secondary pollution.

[0003] Another major advantage of zero-valent iron is its simple operation process and ease of on-site application. Its strong magnetism also facilitates the separation and recovery of materials, increasing its practicality in water treatment processes. However, despite these advantages of zero-valent iron, it also faces some challenges in practical applications. Due to van der Waals forces, high surface energy and magnetic effects, zero-valent iron tends to agglomerate in aqueous solutions, which affects its dispersibility and may reduce treatment efficiency. In addition, zero-valent iron has relatively poor stability and is easily affected by the surrounding environment to form a passivation layer, which further reduces its reduction ability. During migration, zero-valent iron may age rapidly, which limits its long-term effectiveness.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide a biochar-loaded sulfur-modified zero-valent iron material, aiming to solve at least one of the above-mentioned technical problems in the prior art.

[0006] A second object of the present invention is to provide a method for preparing a biochar-loaded sulfur-modified zero-valent iron material.

[0007] The third object of the present invention is to provide an application of biochar-loaded sulfur-modified zero-valent iron material.

[0008] In order to solve the above technical problems, the present invention particularly adopts the following technical solutions:

[0009] A first aspect of the present invention provides a biochar-loaded sulfur-modified zero-valent iron material, in which sulfur-modified zero-valent iron is loaded in the porous structure of the biochar;

[0010] The sulfur-modified zero-valent iron has a core-shell structure;

[0011] The core of the core-shell structure is zero-valent iron, and the shell is iron sulfide.

[0012] Furthermore, the particle size of the biochar-loaded sulfur-modified zero-valent iron material is 100 to 250 nm.

[0013] Furthermore, the element ratio of C:Fe:S in the biochar-loaded sulfur-modified zero-valent iron material is 1-2:1:1-4.

[0014] The second aspect of the present invention provides a method for preparing the biochar-loaded sulfur-modified zero-valent iron material, which comprises pyrolyzing a biomass raw material to obtain biochar, and uniformly mixing iron powder, sulfur powder and the biochar to perform mechanochemical synthesis to obtain the biochar-loaded sulfur-modified zero-valent iron material.

[0015] Furthermore, the temperature rise program of the pyrolysis is:

[0016] The temperature is raised to 500-800°C at a rate of 5-10°C / min, kept at that temperature for 1-3 hours, and then a cooling procedure is performed.

[0017] Furthermore, the pyrolysis is carried out under argon protection.

[0018] Furthermore, the mass ratio of the iron powder, the sulfur powder and the biochar is 1-2:1:1-4, preferably 1-2:1:1-2.

[0019] Furthermore, the mechanochemical synthesis method includes ball milling.

[0020] Furthermore, the ball milling speed is 300-500 rpm, and the time is 3-5 hours.

[0021] The third aspect of the present invention provides the use of the biochar-loaded sulfur-modified zero-valent iron material in groundwater remediation.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] The biochar-loaded sulfur-modified zero-valent iron material provided by the present invention uses sulfur to modify the zero-valent iron, aiming to improve its stability and reactivity. The modification process forms a sulfide layer on the surface of the zero-valent iron, which not only protects the zero-valent iron core from direct contact with water or dissolved oxygen, but also improves its durability. The delocalized electrons in the sulfide layer promote the electron transfer process and enhance the catalytic performance of the material. Biochar, as the substrate of the present invention, not only has excellent adsorption capacity due to its porous structure, but also provides additional adsorption performance and catalytic activity for the material due to its rich active catalytic sites and defective structure. Biochar itself can also act as an electron donor, further enhancing the catalytic efficiency of the material. The biochar-loaded sulfur-modified zero-valent iron material provided by the present invention is not only highly stable, but also has a wide range of applications. The versatility of this material makes it have potential application value in many fields such as environmental remediation and pollutant degradation.

[0024] The preparation method provided by the present invention has simple process, low cost and environmental friendliness because it does not require the addition of chemical reagents. The prepared material has uniform particle size between 100nm and 250nm, regular morphology, good structural characteristics and is suitable for industrial large-scale production.

[0025] The application provided by the present invention provides a material with higher efficiency and more stable performance for groundwater remediation, especially in the treatment process of uranium and metronidazole in water bodies, the adsorption capacity is large and the removal rate is high. The removal rate of uranium can reach 97%, and the removal rate of metronidazole degraded by activated peroxymonosulfate can reach 98%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is the SEM image of the BC / S-ZVI material obtained in Example 1 at a scale of 1 μm;

[0028] Figure 2 This is the SEM image of the BC / S-ZVI material obtained in Example 1 at a scale of 200 nm;

[0029] Figure 3 This is the X-ray diffraction pattern obtained in Characterization Example 2. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations.

[0031] A first aspect of the present invention provides a biochar-loaded sulfur-modified zero-valent iron material, in which sulfur-modified zero-valent iron is loaded in the porous structure of the biochar;

[0032] The sulfur-modified zero-valent iron has a core-shell structure;

[0033] The core of the core-shell structure is zero-valent iron, and the shell is iron sulfide.

[0034] The biochar-loaded sulfur-modified zero-valent iron material provided by the present invention uses sulfur to modify the zero-valent iron, aiming to improve its stability and reactivity. The modification process forms a sulfide layer on the surface of the zero-valent iron, which not only protects the zero-valent iron core from direct contact with water or dissolved oxygen, but also improves its durability. The delocalized electrons in the sulfide layer promote the electron transfer process and enhance the catalytic performance of the material. Biochar, as the substrate of the present invention, not only has excellent adsorption capacity due to its porous structure, but also provides additional adsorption performance and catalytic activity for the material due to its rich active catalytic sites and defective structure. Biochar itself can also act as an electron donor, further enhancing the catalytic efficiency of the material. The biochar-loaded sulfur-modified zero-valent iron material provided by the present invention is not only highly stable, but also has a wide range of applications. The versatility of this material makes it have potential application value in many fields such as environmental remediation and pollutant degradation.

[0035] The biochar-loaded sulfur-modified zero-valent iron (BC / S-ZVI) material provided by the present invention has higher stability than single zero-valent iron, and at the same time, due to the loading of biochar, its adsorption effect is significantly improved. The introduction of biochar not only increases the specific surface area of ​​the material, but also provides more active sites, thereby enhancing the material's adsorption performance for radioactive heavy metal uranium and its ability to degrade metronidazole. The combination of sulfur modification and biochar loading makes the BC / S-ZVI material structure stable and exhibits good cycle performance, effectively improving the deficiencies of single zero-valent iron materials in adsorption performance and cycle effect.

[0036] Furthermore, the particle size of the biochar-loaded sulfur-modified zero-valent iron material is 100 to 250 nm.

[0037] The particle size of BC / S-ZVI material is in the range of 100 to 250 nm, which helps to increase the specific surface area of ​​the material, thereby providing more active sites, which is conducive to improving the adsorption capacity of pollutants and the efficiency of catalytic reactions. Secondly, BC / S-ZVI materials of this particle size have good dispersibility, which can effectively avoid the agglomeration phenomenon like zero-valent iron during use and maintain the high activity of the material during the reaction process. In addition, materials with smaller particle sizes have higher mobility and permeability in the reaction medium, making the contact between pollutants and active sites more complete, improving the kinetic performance of the reaction.

[0038] At the same time, nanometer-scale particle size also helps to improve the reaction kinetics of the material, because smaller particle size means that the diffusion distance between the reactant molecules and the active sites is shortened, thereby accelerating the reaction rate. In addition, materials within this particle size range have a slower sedimentation rate during water treatment, which is conducive to longer contact and treatment, enhancing the effectiveness of the material in practical applications.

[0039] Typically but not limiting, the particle size of the biochar-loaded sulfur-modified zero-valent iron material can be, for example, 100 nm, 125 nm, 150 nm, 175 nm, 200 nm or 250 nm, or any value within the range of 100 nm to 250 nm.

[0040] Furthermore, the element ratio of C:Fe:S in the biochar-loaded sulfur-modified zero-valent iron material is 1-2:1:1-4.

[0041] The second aspect of the present invention provides a method for preparing the biochar-loaded sulfur-modified zero-valent iron material, which comprises pyrolyzing a biomass raw material to obtain biochar, and uniformly mixing iron powder, sulfur powder and the biochar to perform mechanochemical synthesis to obtain the biochar-loaded sulfur-modified zero-valent iron material.

[0042] The preparation method provided by the present invention has simple process, low cost and environmental friendliness because it does not require the addition of chemical reagents. The prepared material has uniform particle size between 100nm and 250nm, regular morphology, good structural characteristics and is suitable for industrial large-scale production.

[0043] Compared with the liquid phase synthesis method, this preparation method provides a more direct and economical synthesis route. This method usually uses mechanical force to act on iron powder, sulfur powder and biochar to promote contact and mixing between the above powdered reactants, thereby stimulating chemical reactions. The advantage of mechanical synthesis is that it can avoid the use of large amounts of solvents, reduce the generation of chemical waste, and comply with the principles of green chemistry. In addition, the operating conditions of the mechanical synthesis method are relatively mild, with low energy consumption, which is suitable for large-scale production, and can reduce reaction time and improve production efficiency. This method also helps to achieve precise control of reaction conditions and improve the purity and uniformity of the product.

[0044] In a specific implementation process, the biomass raw material is typically but not limited to rice straw, corn straw, coconut shell, reed straw or walnut shell.

[0045] Furthermore, the temperature rise program of the pyrolysis is:

[0046] The temperature is raised to 500-800°C at a rate of 5-10°C / min, kept at that temperature for 1-3 hours, and then a cooling procedure is performed.

[0047] Before pyrolysis, the biomass raw materials need to be crushed to improve the efficiency of pyrolysis. During the pyrolysis process, the biomass raw materials first undergo dehydration and thermal decomposition, in which water and volatile components are released, and then high molecular organic substances such as cellulose, hemicellulose and lignin begin to decompose into smaller hydrocarbons and char. The biochar generated by the pyrolysis process has a high specific surface area and porosity.

[0048] The present invention uses biochar because biochar is derived from renewable biomass resources, has better environmental sustainability, and helps reduce dependence on fossil fuels. Secondly, biochar usually has a high degree of porosity and a large specific surface area, which provides more active sites for loading sulfur-modified zero-valent iron, enhancing the adsorption capacity and catalytic performance of the material. In addition, the pore structure of biochar helps to improve the dispersibility and stability of the material, reduce the agglomeration of sulfur-modified zero-valent iron, and thus maintain its long-term reactivity. The surface of biochar is rich in oxygen-containing functional groups, which can form strong chemical bonds with sulfur-modified zero-valent iron, further improving the structural stability and reaction selectivity of the material.

[0049] Typically but not restrictively, the rate during the heating process can be, for example, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, or any value in the range of 5°C / min to 10°C / min; the target temperature to which the temperature is raised can be, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, or any value in the range of 500°C to 800°C; the holding time can be, for example, 1h, 1.5h, 2h or 3h, or any value in the range of 1h to 3h.

[0050] Furthermore, the pyrolysis is carried out under argon protection.

[0051] Furthermore, the mass ratio of the iron powder, the sulfur powder and the biochar is 1-2:1:1-4, preferably 1-2:1:1-2.

[0052] The mass ratio of the iron powder, the sulfur powder and the biochar is within the above-mentioned ratio range, which ensures the synergistic effect between the components, making the sulfur-modified zero-valent iron more dispersible on the biochar, thereby improving the reactivity and stability of the overall material.

[0053] The addition of sulfur powder within the above-mentioned proportion range helps to form a sulfide layer on the surface of zero-valent iron, which not only enhances the corrosion resistance of the material, but also improves its promoting effect on electron transfer, thereby improving the catalytic performance of the material.

[0054] The proportion of biochar within the above range not only provides a porous substrate with high specific surface area and increases the adsorption sites, but also enhances the interaction with sulfur-modified zero-valent iron through its oxygen-containing functional groups, thereby improving the loading capacity and structural stability of the material.

[0055] Typically but not limitatively, the mass ratio of the iron powder, the sulfur powder and the biochar can be 1:1:1, 1:1:2, 1:1:3, 2:1:1, 2:1:2, 2:1:4 or 2:1:3, or any ratio value within the range of 1 to 2:1:1 to 4; the preferred mass ratio can be 1:1:1, 1.5:1:1.5, 2:1:1.5 or 2:1:2, or any ratio value within the range of 1 to 2:1:1 to 2.

[0056] Furthermore, the mechanochemical synthesis method includes ball milling.

[0057] Furthermore, the ball milling speed is 300-500 rpm, and the time is 3-5 hours.

[0058] Typically but not limiting, the rotation speed of the ball mill can be, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm, or any value within the range of 300 rpm to 500 rpm; the ball milling treatment time can be, for example, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, or any value within the range of 3 h to 5 h.

[0059] The third aspect of the present invention provides the use of the biochar-loaded sulfur-modified zero-valent iron material in groundwater remediation.

[0060] The application provided by the present invention provides a material with higher efficiency and more stable performance for groundwater remediation, especially in the treatment process of uranium and metronidazole in water bodies, the adsorption capacity is large and the removal rate is high. The removal rate of uranium can reach 97%, and the removal rate of metronidazole degraded by activated peroxymonosulfate can reach 98%. It can specifically remove target pollutants in complex water environments, reduce the removal of beneficial components in water bodies, and protect the water ecological balance.

[0061] In the specific use process, when adsorbing uranium in water, the uranium concentration is controlled at 5-40 mg / L, which has a better adsorption effect. The dosage of BC / S-ZVI material is 0.1-0.6 g / L, and the adsorption capacity of BC / S-ZVI material is 21.24 mg / g.

[0062] When removing metronidazole from water, BC / S-ZVI material degrades metronidazole by activating peroxymonosulfate. Specifically, BC / S-ZVI material can promote the decomposition of peroxymonosulfate to produce highly active sulfate radicals (SO4· - ) and hydroxyl radicals (·OH), which have extremely strong oxidizing ability and can indiscriminately attack the active groups in the metronidazole molecule, causing it to mineralize or transform into low-toxic small molecules. The adsorption of biochar in the BC / S-ZVI material can initially enrich metronidazole, bringing it closer to the catalytic active site and improving the degradation efficiency.

[0063] In the specific use process, when degrading metronidazole in water, the metronidazole concentration is controlled at 5-30 mg / L, the addition amount of permonosulfate is 0.1-1 mmol / L, and the addition amount of BC / S-ZVI material is 0.05-0.5 g / L.

[0064] In the following, some embodiments of the present invention are described in detail in conjunction with the embodiments. In the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. The raw materials used in the present invention can be obtained by commercial purchase unless otherwise specified.

[0065] Example 1

[0066] This embodiment provides a BC / S-ZVI material, and the preparation process is as follows:

[0067] 1. Place 10 g of rice straw powder in a corundum crucible, raise the temperature to 800 °C at 10 °C / min in a tube furnace, and pyrolyze for 2 h to obtain black biochar powder.

[0068] 2. The iron powder, sulfur powder and the biochar obtained in step 1 were uniformly mixed in a ball mill at a mass ratio of 1:1:2, stainless steel beads were added, the ball mill speed was set to 400 r / min, and the ball milling time was 4 h to obtain BC / S-ZVI material.

[0069] Example 2

[0070] This embodiment provides a BC / S-ZVI material. The difference from Embodiment 1 is that the mass ratio of iron powder, sulfur powder and biochar is 1:1:1. The other steps are the same as those in Embodiment 1 and will not be repeated here.

[0071] Example 3

[0072] This embodiment provides a BC / S-ZVI material. The difference from Embodiment 1 is that the mass ratio of iron powder, sulfur powder and biochar is 1:1:4. The other steps are the same as those in Embodiment 1 and will not be repeated here.

[0073] Example 4

[0074] This embodiment provides a BC / S-ZVI material. The difference from Embodiment 1 is that the mass ratio of iron powder, sulfur powder and biochar is 2:1:4. The other steps are the same as those in Embodiment 1 and will not be repeated here.

[0075] Example 5

[0076] This embodiment provides a BC / S-ZVI material, and the preparation process is as follows:

[0077] 1. Place 10 g corn straw powder in a corundum crucible, raise the temperature to 800 °C at 10 °C / min in a tube furnace, and pyrolyze for 2 h to obtain black biochar powder.

[0078] 2. Same as the step in Example 2.

[0079] Example 6

[0080] This embodiment provides a BC / S-ZVI material, and the preparation process is as follows:

[0081] 1. Place 10 g of rice straw powder in a corundum crucible, raise the temperature to 700 °C at 10 °C / min in a tube furnace, and pyrolyze for 2 h to obtain black biochar powder.

[0082] 2. Same as the step in Example 2.

[0083] Example 7

[0084] This embodiment provides a BC / S-ZVI material. The difference from Embodiment 1 is that the mass ratio of iron powder, sulfur powder and biochar is 2:1:4. The other steps are the same as those in Embodiment 1 and will not be repeated here.

[0085] Example 8

[0086] This embodiment provides a BC / S-ZVI material. The difference from Embodiment 1 is that the mass ratio of iron powder, sulfur powder and biochar is 1:2:1. The other steps are the same as those in Embodiment 1 and will not be repeated here.

[0087] Example 9

[0088] This embodiment provides a BC / S-ZVI material. The difference from Embodiment 1 is that the mass ratio of iron powder, sulfur powder and biochar is 4:1:1. The other steps are the same as those in Embodiment 1 and will not be repeated here.

[0089] Example 10

[0090] This embodiment provides a BC / S-ZVI material. The difference from Embodiment 1 is that the mass ratio of iron powder, sulfur powder and biochar is 1:1:4. The other steps are the same as those in Embodiment 1 and will not be repeated here.

[0091] Comparative Example 1

[0092] This comparative example provides a zero-valent iron material, which is an iron powder, and is of the same specification and the same batch as the iron powder used in the embodiment.

[0093] Comparative Example 2

[0094] This comparative example provides a sulfur-modified zero-valent iron (abbreviated as S-ZVI) material, which is prepared by a sodium sulfide loading method. Iron powder is placed in an acetic acid-sodium acetate buffer solution and anaerobically shaken for 10 minutes to make Fe 2+ After full release, add Na2S to the system, continue to shake at constant temperature for 12 hours, then filter, freeze-dry for 2 hours, and seal and store for later use.

[0095] Characterization Example 1

[0096] The BC / S-ZVI material obtained in Example 1 was subjected to scanning electron microscopy, and the SEM images obtained at a scale of 1 μm and 200 nm corresponded to the following: Figure 1 and Figure 2 shown.

[0097] from Figure 1It can be observed that there are smooth zero-valent iron spherical particles on the surface of biochar, the particle size is uneven, and the particles are connected together in a chain, which may be caused by ball milling. During the ball milling process, the chain iron particles are distributed on the biochar to form a ternary complex of BC, S and ZVI, forming a heterogeneous filler, and the surface is coated with carbon plates to prevent new ZVI from generating a passivation layer.

[0098] from Figure 2 It can be seen that sulfur forms a thin film on the surface of zero-valent iron particles due to the formation of an outer layer containing a large amount of iron sulfide and a small amount of iron oxide, and it is loaded on the biochar.

[0099] Characterization Example 2

[0100] The BC / S-ZVI material, iron powder (abbreviated as ZVI), biomass carbon (abbreviated as BC) in Example 2 and the S-ZVI material obtained in Comparative Example 2 were X-ray diffraction patterns. The obtained diffraction patterns are as follows: Figure 3 shown.

[0101] from Figure 3 It can be seen that the characteristic peaks of BC and ZVI are both present in BC / S-ZVI, and the peak intensities of the (200) and (110) crystal planes of the prepared BC / S-ZVI are relatively high, indicating that the biochar-loaded sulfur-modified zero-valent iron BC / S-ZVI material was successfully prepared.

[0102] Test Example 1

[0103] The materials obtained in the examples and comparative examples were used as adsorbents to carry out solution U(VI) adsorption tests.

[0104] The U(VI) aqueous solution used in the adsorption experiment was prepared by diluting 1g / L uranium standard solution. The initial U(VI) mass concentration was 10mg / L, the pH was adjusted to 6 with 0.1mol / L HCl and NaOH solution, the adsorbent dosage was 0.1g / L, the reaction temperature was 30℃, and the reaction time was 3h. The pH was adjusted with 0.1mol / L HCl and NaOH solution.

[0105] Place the adsorbent in a conical flask containing 100 mL of U(VI) aqueous solution and shake it on a shaker at 220 r / min. After the shaking is completed, filter it through a 0.45 μm filter membrane and determine the concentration of uranium U(VI) in the filtrate using a UV-visible spectrophotometer.

[0106] The obtained data are shown in Table 1 below.

[0107] Table 1

[0108]

[0109]

[0110] It can be seen from Table 1 that when the composite ratio is 1:1:1, the material has the best adsorption effect on uranium U(VI); among many biomass raw materials, rice straw has certain advantages in preparing this composite material; in addition, the roasting temperature of biochar has a great influence on the performance of the material. Experiments have shown that the higher the temperature, the better the adsorption performance of the material; finally, by comparing the composite material with zero-valent iron ZVI and sulfur-modified zero-valent iron S-ZVI, it can be found that the composite material has significant advantages in removing uranium U(VI) from groundwater.

[0111] Test Example 2

[0112] The materials obtained in the examples and comparative examples were tested for degradation of metronidazole.

[0113] Two sets of tests were performed for each group of materials:

[0114] The first set of tests: 10 mg of material and 0.5 mmol / L potassium persulfate (PMS) were weighed and added into 100 mL of 10 mg / L metronidazole solution.

[0115] The second set of tests: 10 mg of the material was weighed and added to 100 mL of 10 mg / L metronidazole solution.

[0116] The above solution was placed in a shaker and shaken at a speed of 220 r / min for 2 hours to carry out an activation degradation experiment. After completion, the metronidazole content in the solution was measured. The obtained data are shown in Table 2 below.

[0117] Table 2

[0118]

[0119]

[0120] It can be seen from Table 2 that compared with zero-valent iron ZVI and sulfur-modified zero-valent iron S-ZVI, the composite material BC / S-ZVI can better remove metronidazole from water. At the same time, it can be seen from the two sets of test results that the adsorption effect of the material itself on metronidazole is negligible and can be ignored. It is mainly removed by adding peroxymonosulfate to activate the material for advanced oxidation.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A biochar-loaded sulfur-modified zero-valent iron material, characterized in that: Sulfur-modified zero-valent iron is loaded in the porous structure of biochar; The sulfur-modified zero-valent iron has a core-shell structure; The core of the core-shell structure is zero-valent iron, and the shell is iron sulfide.

2. The biochar-loaded sulfur-modified zero-valent iron material according to claim 1, characterized in that: The particle size is 100~250nm.

3. The biochar-loaded sulfur-modified zero-valent iron material according to claim 1, characterized in that: The element ratio of C:Fe:S is 1-2:1:1-4.

4. A method for preparing the biochar-supported sulfur-modified zero-valent iron material according to any one of claims 1 to 3, characterized in that: The biomass raw material is pyrolyzed to obtain biochar, and iron powder, sulfur powder and the biochar are evenly mixed to perform mechanochemical synthesis to obtain the biochar-loaded sulfur-modified zero-valent iron material.

5. The preparation method according to claim 4, characterized in that: The temperature rise program of the pyrolysis is: The temperature is raised to 500-800°C at a rate of 5-10°C / min, kept at that temperature for 1-3 hours, and then a cooling procedure is performed.

6. The preparation method according to claim 4, characterized in that: The pyrolysis was carried out under argon protection.

7. The preparation method according to claim 4, characterized in that: The mass ratio of the iron powder, the sulfur powder and the biochar is 1-2:1:1-4, preferably 1-2:1:1-2.

8. The preparation method according to claim 4, characterized in that: The mechanochemical synthesis method includes ball milling.

9. The preparation method according to claim 8, characterized in that: The ball mill has a rotation speed of 300 to 500 rpm and a milling time of 3 to 5 hours.

10. Use of the biochar-loaded sulfur-modified zero-valent iron material according to any one of claims 1 to 3 in groundwater remediation.

Citation Information

Cited By

  • Modified iron heterojunction biomass slow-release material, preparation method thereof and application of coupled electric field in remediation of organic pollutants in underground water

    CN121892173A

  • Modified iron heterojunction biomass slow-release material, preparation method thereof and application of coupling electric field in remediation of groundwater organic pollutants

    CN121892173B